IMPROVE THE QUALITY OF TEACHING IN FOREIGN LANGUAGE TEACHING AND DEVELOP INTERCULTURAL RELATIONSHIPS AMONG STUDENTS - Tulaboyeva, Gulorom (Журнал иностранных языков и лингвистики, 2023)
In our article, the question of the development of intercultural communication between English-speaking students, is the most relevant at the moment, where the relationship between peoples, languages, and cultures has reached an unprecedented level and, as always, the issue of tolerance of interest to them is considered. Respect, because it awakens, overcoming alien cultures. a feature of self-esteem through abundance, lack, or simply differences in other cultures.